Multi-component doped supercapacitor electrode based on laser direct writing and preparation method thereof

Multi-component doping is achieved in graphene electrodes through laser direct writing technology, solving the problem of limited doping performance of single-component, improving the conductivity and stability of supercapacitors, meeting high-performance requirements, and suitable for industrial production.

CN119170420APending Publication Date: 2024-12-20SUZHOU UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411184180.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Existing supercapacitor electrodes have limitations in performance improvement, especially the single component doping is difficult to meet high performance requirements, and there are problems of stability and insufficient energy density.

Method used

Using laser direct writing technology to prepare multi-component doped graphene electrodes in one step, through the mixing of metal salt solution and organic compound solution, laser direct writing, etc., the in-situ co-doping of multiple metal/metal oxide components is achieved. , improve the performance of the electrode.

Benefits of technology

It realizes the efficient preparation of multi-component doped electrodes, improves the conductivity, stability and energy density of the electrodes, and provides a new way to high-performance supercapacitors, suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170420A_ABST
    Figure CN119170420A_ABST
Patent Text Reader

Abstract

The invention relates to a multi-component doped supercapacitor electrode based on laser direct writing and a preparation method thereof, and belongs to the technical field of supercapacitors. The preparation method of the multi-component doped supercapacitor electrode based on laser direct writing comprises the following steps: mixing a metal salt solution with an organic compound solution containing a reducing group to obtain a precursor solution; carrying out cleaning and hydrophilic treatment on the substrate to obtain a pretreated substrate; coating the pre-treated substrate with the obtained precursor solution, and drying to obtain a precursor film; and performing laser direct writing on the obtained precursor film according to a preset pattern to obtain the multi-component doped supercapacitor electrode based on laser direct writing. The method is simple in technology, low in cost and high in preparation speed. And by utilizing a laser direct writing technology, the cost can be reduced, and industrial production is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of supercapacitors, and in particular to a multi-component doped supercapacitor electrode based on laser direct writing and a preparation method thereof. Background Art

[0002] With the development of science and technology and social progress, human demand for energy has further increased, which in turn has led to the rapid development of energy storage devices. The existing energy storage methods are mainly various types of batteries, such as lithium batteries, fuel cells, etc. However, most of the batteries currently on the market have poor cycle stability and safety issues, and explosions and injuries caused by internal short circuits in batteries are not uncommon. Therefore, finding a high-performance, low-cost, and stable energy storage device has become a research hotspot in the current scientific field. Supercapacitors

[0003] (Electrochemical capacitors) have many advantages such as ultrafast charge / discharge rate, high energy density, good cycle stability, etc., and have attracted widespread attention in recent years. Typical supercapacitors are mainly composed of two parts: electrodes and electrolytes, among which the electrode is one of the important factors determining the performance of supercapacitors. In recent years, graphene has been widely used to prepare supercapacitor electrodes. The energy storage mechanism of graphene electrodes is typical of double-layer capacitance. During operation, electrolyte ions will desorb and store charges on its surface and electrolyte interface, and there is no change in the element valence state of the electrode and electrolyte. Since energy storage occurs at the interface, reversible electrolyte ion adsorption and desorption can achieve extremely long service life and high power density of supercapacitors, but its energy density is poor. To solve this problem, researchers proposed to dope pseudocapacitive components (such as metals and metal oxide nanomaterials) in graphene, and use the reversible oxidation-reduction reaction (i.e., Faraday process) of such materials in the electrochemical process to improve the energy density of the electrode.

[0004] The main methods for preparing graphene include chemical vapor deposition (CVD), redox method, micromechanical exfoliation method, etc. The synthesis method of nanomaterials such as metal / metal oxides is typically hydrothermal method. After the preparation of the two, they need to be further mixed into a composite material, and the electrode preparation is completed through subsequent graphics, post-processing and other methods. In recent years, laser direct writing technology has shown obvious advantages in the preparation of supercapacitor electrodes due to its advantages such as non-contact, maskless, low cost and high efficiency. Among them, laser-induced graphene technology uses a flexible polymer substrate as a precursor, destroys the chemical bonds therein through the light-heat / chemical action caused by focused laser irradiation, and releases gases such as carbon dioxide while rearranging carbon atoms into graphene, realizing the one-step preparation of porous graphene, and its porous characteristics can provide sufficient sites for electrochemical reactions. Based on this, researchers have achieved in-situ doping of various pseudocapacitive components (such as manganese dioxide, iron trioxide, cobalt oxide, etc.) by depositing metals on its surface, coating pre-synthesized nanomaterials, and metal ion precursor films. Among them, the metal ion precursor can be prepared by simply mixing the metal ions with the film-forming components, etc., which is fast, simple and efficient. However, the prior art only achieves the doping of a single component, which has limited contribution to the performance improvement of graphene-based electrodes. For example, pseudocapacitor components such as nickel and copper have extremely high theoretical specific capacity, but low stability. Components represented by cobalt-based materials have high stability but insufficient theoretical specific capacity. Precious metal materials such as silver have excellent conductivity but lack the multi-level oxidation-reduction valence characteristics of the above-mentioned pseudocapacitor system components. If the in-situ co-doping of the above-mentioned multiple components in laser-induced graphene can be achieved, the performance advantages of each component can be effectively integrated, providing new ideas for the construction of high-performance supercapacitors.

[0005] Existing studies have shown that by doping a metal / metal oxide component in the graphene precursor through single-component doping based on laser direct writing technology, the overall performance of supercapacitors can be improved to a certain extent. However, single-component doping has performance limitations and it is difficult to meet the future industrial production needs for high-performance supercapacitors. If multi-component co-doping of supercapacitor electrodes can be achieved, it is expected that the performance of supercapacitors will be further improved through the synergistic effect of multiple components. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides a multi-component doped supercapacitor electrode based on laser direct writing and a preparation method thereof. The present invention uses laser induced graphene technology to prepare electrodes doped with two or more metal / metal oxide components in one step, providing a new way to manufacture high-performance supercapacitors.

[0007] The present invention is achieved through the following technical solutions:

[0008] The first object of the present invention is to provide a method for preparing a multi-component doped supercapacitor electrode based on laser direct writing, comprising the following steps:

[0009] (1) mixing a metal salt solution with an organic compound solution containing a reducing group to obtain a precursor solution;

[0010] (2) cleaning and hydrophilizing the substrate to obtain a pretreated substrate;

[0011] (3) coating the precursor solution obtained in step (1) on the pretreated substrate obtained in step (2), and obtaining a precursor film after drying;

[0012] (4) performing laser direct writing on the precursor film obtained in step (3) according to a preset pattern to obtain a multi-component doped supercapacitor electrode based on laser direct writing.

[0013] In one embodiment of the present invention, in step (1), the metal salt in the metal salt solution is selected from two or more soluble metal salts such as copper salts, nickel salts, silver salts, iron salts, manganese salts and cobalt salts.

[0014] In one embodiment of the present invention, the metal salt is a soluble metal salt coordinated by anions such as nitrate and sulfate.

[0015] In one embodiment of the present invention, in step (1), the concentration of the heavy metal salt in the metal salt solution is 2 mol / L to 6 mol / L.

[0016] In one embodiment of the present invention, in step (1), the organic compound in the organic compound solution containing a reducing group is selected from one or more of polyvinyl pyrrolidone, formic acid, oxalic acid and polyethylene glycol.

[0017] In one embodiment of the present invention, in step (1), the concentration of the organic compound in the organic compound solution containing a reducing group is 0.1 g / mL to 0.3 g / mL;

[0018] And / or, the volume ratio of the organic compound solution containing reducing groups to the metal salt solution is 3:1 to 1:1.

[0019] In one embodiment of the present invention, in step (2), the substrate is selected from one of polyimide, polyethylene terephthalate and polycarbonate.

[0020] In one embodiment of the present invention, in step (2), the hydrophilic treatment is performed by a plasma machine; an atmospheric atmosphere is used, a vacuum degree ≥ 98%, a plasma power of 30W to 80W, and a treatment time of about 8min to 10min.

[0021] In one embodiment of the present invention, in step (3), the coating is selected from spin coating and / or rod coating.

[0022] In one embodiment of the present invention, in step (3), the drying conditions are: drying at 70° C. to 80° C. for 10 min to 15 min.

[0023] In one embodiment of the present invention, in step (4), the parameters of the laser direct writing are: power 0.5W to 3W, spot diameter 20μm to 500μm, scanning interval less than 300μm, and scanning speed 5mm / s to 20mm / s.

[0024] The second object of the present invention is to provide a multi-component doped supercapacitor electrode based on laser direct writing prepared by the preparation method.

[0025] The third object of the present invention is to provide an application of the multi-component doped supercapacitor electrode based on laser direct writing in the preparation of a supercapacitor.

[0026] The above technical solution of the present invention has the following advantages compared with the prior art:

[0027] (1) The present invention provides a multi-component doped supercapacitor electrode based on laser direct writing and a preparation method thereof. The laser in-situ action can reduce the metal salt while inducing graphene near the surface of the flexible substrate. The components can be customized arbitrarily. The present invention has simple technology, low cost and fast preparation speed. The use of laser direct writing technology can reduce costs and realize industrial production.

[0028] (2) The method of the present invention can efficiently prepare multi-component doped electrodes. The obtained multi-component metals will realize atomic-scale solid solution or in-situ alloying under the action of instantaneous light and heat, and effectively utilize the synergistic effect of each component to improve device performance: for example, the high conductivity component will effectively promote charge transfer, and the pseudocapacitive component in the alloy / solid solution will be more susceptible to redox, further enhancing the energy density; under the action of solid solution of the high stability component, the structural collapse of the pseudocapacitive component can be effectively suppressed, thereby improving its overall stability; under the co-doping of multi-component pseudocapacitors, by utilizing their different reaction potentials, multi-stage redox reactions can be introduced under the premise of the same doping amount to maximize the pseudocapacitive contribution. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:

[0030] Figure 1 This is a schematic diagram of the process of preparing multi-component co-doped graphene based on laser direct writing in Example 1 of the present invention;

[0031] Figure 2 This is a low-magnification microscopic morphology of the copper-silver co-doped graphene electrode based on laser direct writing in Example 1 of the present invention;

[0032] Figure 3 This is a high-magnification microscopic morphology and corresponding element distribution diagram of the copper-silver co-doped graphene electrode based on laser direct writing in Example 1 of the present invention;

[0033] Figure 4 The cyclic voltammetric characteristic curve (A) and the constant current charge-discharge curve (B) of the copper-silver co-doped graphene electrode based on laser direct writing in Example 2 of the present invention;

[0034] Figure 5 The cyclic voltammetric characteristic curve (A) and the constant current charge-discharge curve (B) of the nickel-cobalt co-doped graphene electrode based on laser direct writing in Example 3 of the present invention;

[0035] Figure 6 The macroscopic morphology of the interdigitated electrode of the copper-silver co-doped graphene electrode based on laser direct writing in the application example of the present invention;

[0036] Figure 7 The cyclic voltammetric characteristic curves of copper-silver co-doped, copper-doped, and silver-doped graphene supercapacitors based on laser direct writing in the application example of the present invention. DETAILED DESCRIPTION

[0037] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0038] The first aspect of the present invention provides a method for preparing a multi-component doped supercapacitor electrode based on laser direct writing, and the specific steps are as follows:

[0039] Step 1: dissolving 2 mol / L to 6 mol / L of a metal salt in deionized water to prepare a metal salt solution; optionally, the metal salt solution in step 1 is selected from two or more water-soluble metal salts such as cobalt nitrate, silver nitrate, nickel nitrate, and copper nitrate;

[0040] Step 2: dissolving an organic compound having a reducing group (hydroxyl or carboxyl) in deionized water to prepare 0.1 g / mL to 0.3 g / mL of a reducing agent;

[0041] Optionally, the reducing agent in step 2 is selected from high molecular organic compounds containing hydroxyl groups, carboxyl groups, etc., such as polyvinyl pyrrolidone, formic acid, oxalic acid, polyethylene glycol, etc.;

[0042] Step 3: Evenly mix the metal salt solution in step 1 and the reducing agent in step 2 in a volume ratio of 3:1 to 1:1 to prepare the desired precursor solution;

[0043] Step 4: cutting the flexible polymer substrate into a desired size, washing it with deionized water and ethanol, and subjecting it to a hydrophilic treatment;

[0044] Optionally, the flexible polymer substrate used in step 4 is selected from one of polyimide, polyethylene terephthalate, and polycarbonate;

[0045] Optionally, the hydrophilicity in step 4 is carried out by a plasma machine, using an atmospheric atmosphere, a vacuum degree of not less than 98%, a plasma power of about 30W to 80W, and a treatment time of about 8min to 10min;

[0046] Step 5: Take an appropriate amount of precursor solution and evenly apply it on the surface of the substrate by spin coating, rod coating, etc.;

[0047] Step 6: Place the treated substrate on a heating platform and dry it at a certain temperature to form a uniform film;

[0048] Preferably, the temperature in step 6 is set to 70°C to 80°C for drying, and the drying time is 10min to 15min;

[0049] Step 7: placing the substrate prepared with the precursor film on a laser processing platform;

[0050] Step 8: Draw the required graphics through the graphical software and import them into the software system, adjust the laser parameters, and prepare the electrodes through laser direct writing technology, such as Figure 1 As shown;

[0051] Preferably, the laser parameters in step eight are power 0.5W to 3W, spot diameter 20μm to 500μm, scanning interval less than 300μm, and scanning speed 5mm / s to 20mm / s;

[0052] Step nine: Rinse the residual precursor solution with deionized water and dry it at room temperature to prepare a multi-component doped supercapacitor electrode.

[0053] The second aspect of the present invention provides a multi-component doped supercapacitor electrode based on laser direct writing prepared by the preparation method.

[0054] The third aspect of the present invention provides the use of the multi-component doped supercapacitor electrode based on laser direct writing in the preparation of a supercapacitor.

[0055] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods, and the materials, reagents, etc. used are all available from commercial sources unless otherwise specified.

[0056] Example 1

[0057] This embodiment provides a method for preparing a copper-silver co-doped graphene electrode based on laser direct writing, comprising the following steps:

[0058] (1) preparing a precursor solution by mixing 6 mol / L copper nitrate solution, 6 mol / L silver nitrate solution, and 0.3 g / mL polyvinyl pyrrolidone aqueous solution in a volume ratio of 3:1:2;

[0059] (2) A polyimide substrate with a thickness of 200 μm was cut into 25×50 mm, cleaned with deionized water and alcohol and air-dried, and hydrophilic treated by a plasma cleaning machine; an atmospheric atmosphere was used, the vacuum degree was not less than 98%, the plasma power was about 50 W, and the treatment time was about 8 to 10 minutes;

[0060] (3) Using a pipette, take 60 μL of the precursor solution obtained in step (1), evenly apply it on the substrate treated in step (2), and place it on a 70° C. heating platform to dry to obtain a precursor film;

[0061] (4) placing the processed substrate together with the glass slide on a laser processing platform with a wavelength of 1064 nm, and using a heating platform to continuously heat to prevent the precursor film from liquefying, setting the laser power to 3.2 W, the scanning speed to 10 mm / s, the scanning gap to 15 μm, the spot diameter to about 20 μm, and the scanning number to 1;

[0062] Figure 2 This is a low-magnification microscopic morphology of the obtained copper-silver co-doped graphene electrode. It can be seen that the obtained electrode is mainly composed of a lamellar structure, indicating that the graphene structure was successfully prepared under laser induction;

[0063] Figure 3 The high-magnification microscopic morphology and corresponding element distribution of the obtained copper-silver co-doped graphene electrode. It can be seen that a large number of nanoparticles are attached to the surface of the obtained graphene structure, and the nanoparticles are mainly copper and silver elements. The quantitative analysis of the energy spectrum shows that the mass proportions of copper, silver and carbon in the structure are 7.5%, 11.9% and 73.8% respectively, indicating that the co-doping of copper and silver components has been successfully achieved.

[0064] Example 2

[0065] This embodiment provides a method for preparing a copper-silver co-doped graphene electrode based on laser direct writing, and characterizes its energy storage characteristics by an electrochemical method, comprising the following steps:

[0066] (1) 3 mol / L copper nitrate solution, 2 mol / L silver nitrate solution, and 0.3 g / mL polyvinyl pyrrolidone aqueous solution were mixed in a volume ratio of 1:1:2 to prepare a precursor solution. Compared with Example 1, it can be seen that the content of the doping component can be customized by the precursor concentration;

[0067] (2) A polyimide substrate with a thickness of 200 μm was cut into 25×50 mm, cleaned with deionized water and alcohol and air-dried, and hydrophilic treated by a plasma cleaning machine; an atmospheric atmosphere was used, the vacuum degree was not less than 98%, the plasma power was about 50 W, and the treatment time was about 8 to 10 minutes;

[0068] (3) Using a pipette, take 20 μL of the precursor solution prepared in step (1), evenly apply it on the substrate treated in step (2), and place it on a 70° C. heating platform to dry to obtain a precursor film;

[0069] (4) The processed substrate and the glass slide were placed on a laser processing platform with a wavelength of 532 nm. At the same time, a heating platform was used for continuous heating to prevent the precursor film from liquefying. The laser power was set to 1.9 W, the spot diameter was 500 μm, the speed was 5 mm / s, and the interval was 0.1 mm.

[0070] Energy storage characteristics evaluation:

[0071] The obtained electrode was cut into 1×1 cm 2 size, and used it as the working electrode, using a commercial 1×1cm 2 Platinum sheet was used as the counter electrode and commercial mercury / mercuric oxide was used as the reference electrode to form a three-electrode system, and the electrochemical performance was tested in a 6 mol / L KOH electrolyte solution.

[0072] Figure 4 The cyclic voltammetric characteristic curve and the corresponding constant current charge-discharge curve of the copper-silver co-doped graphene electrode. It can be seen from the voltammetric characteristic curve that as the scan rate increases from 20mV / s to 100mV / s, the curve in the selected voltage range of -0.2V to 0.6V is nearly rectangular and has good symmetry, indicating good energy storage characteristics. Among them, two oxidation peaks are observed at around 0.3V and 0.4V, and two corresponding reduction peaks are observed at around 0V and 0.1V, indicating that the valence state of the doped copper and silver components has changed, which is beneficial to improve the electrode energy storage performance. The characteristics shown by the constant current charge-discharge curve are consistent with the cyclic voltammetric characteristic curve.

[0073] Example 3

[0074] This embodiment provides a method for preparing a nickel-cobalt co-doped graphene electrode based on laser direct writing, and characterizes its energy storage characteristics by an electrochemical method, comprising the following steps:

[0075] (1) preparing a precursor solution by mixing 3 mol / L nickel nitrate solution, 3 mol / L cobalt nitrate solution, and 0.3 g / ml polyvinyl pyrrolidone aqueous solution in a volume ratio of 1:1:2;

[0076] (2) A polyimide substrate with a thickness of 200 μm was cut into 25×50 mm, cleaned with deionized water and alcohol and air-dried, and hydrophilic treated by a plasma cleaning machine; an atmospheric atmosphere was used, the vacuum degree was not less than 98%, the plasma power was about 50 W, and the treatment time was about 8 to 10 minutes;

[0077] (3) Using a pipette, take 100 μL of the precursor solution prepared in step (1), evenly apply it on the substrate treated in step (2), and place it on a 70° C. heating platform to dry to obtain a precursor film;

[0078] (4) The processed substrate and the glass slide were placed on a laser processing platform with a wavelength of 532 nm. The heating platform was used for continuous heating to prevent the precursor film from liquefying. The laser power was set to 178 mW, the scanning speed to 5 mm / s, the scanning gap to 0.1 mm, and the number of scans to 1.

[0079] The electrode performance was evaluated using the electrochemical method described in Example 2. Figure 5 The cyclic voltammetric characteristic curve and the corresponding constant current charge-discharge curve of the nickel-cobalt co-doped graphene electrode. It can be seen from the voltammetric characteristic curve that as the scan rate increases from 20mV / s to 100mV / s, the curve in the selected voltage range of -0.2V to 0.6V is nearly rectangular and has good symmetry, indicating that it has good energy storage characteristics. Among them, the presence of oxidation peaks and reduction peaks are observed at around 0.4V and 0.2V, respectively, indicating that the valence state of the doped nickel-cobalt components has changed, which is beneficial to improving the energy storage performance of the electrode. The characteristics shown by the constant current charge-discharge curve are consistent with the cyclic voltammetric characteristic curve.

[0080] Comparative Example

[0081] This comparative example provides a method for preparing a single-component copper or single-component silver-doped graphene electrode based on laser direct writing. The preparation method is similar to that of Example 1, except that in step (1), the precursor contains only single-component copper nitrate or single-component silver nitrate.

[0082] Application Examples

[0083] This embodiment provides a method for assembling a quasi-solid-state supercapacitor based on a copper-silver co-doped graphene electrode, and characterizes its energy storage characteristics by an electrochemical method, comprising the following steps:

[0084] (1) Mix 1 g of polyvinyl alcohol with 10 mL of deionized water and stir at 80° C. for about 2 hours until the polyvinyl alcohol is completely dissolved;

[0085] (2) After the above solution is cooled to 50°C, 1.2 g of potassium hydroxide dissolved in 2 mL of deionized water is added dropwise;

[0086] (3) The obtained mixed solution is allowed to stand and is cooled naturally to room temperature to obtain the gel electrolyte used in the experiment;

[0087] (4) Designing interdigital electrodes using CAD drawing software, and preparing interdigital electrodes using the laser direct writing parameters described in Example 1; Figure 6 As shown, it can be seen that laser direct writing technology can realize the customization of any graphics, which is efficient, convenient and widely applicable;

[0088] (5) Using commercial conductive silver paste, apply it to the electrodes on both sides to enhance conductivity, and cover them with polyimide tape, leaving the middle interdigitated fingers as the working area, and then drop-coat the gel electrolyte on the working area to prepare the resulting solid-state supercapacitor;

[0089] (6) connecting the electrodes on both sides to the working electrode and the reference electrode / counter electrode of the electrochemical workstation to form a dual-electrode system, and performing an electrochemical performance test on the obtained solid-state supercapacitor;

[0090] The comparative example used a similar method to assemble a quasi-solid-state supercapacitor, and then characterized its energy storage characteristics by electrochemical methods.

[0091] Figure 7 The cyclic voltammetric characteristic curves of the obtained copper-silver and copper-silver solid-state supercapacitors are shown. From the results, it can be seen that the curve integral area of ​​the solid-state capacitor under copper-silver dual-component doping is significantly higher than that of the single-component one, indicating that the co-doped electrode has a higher energy density and better performance.

[0092] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A method for preparing a multi-component doped supercapacitor electrode based on laser direct writing, characterized in that: The following steps are involved: (1) mixing a metal salt solution with an organic compound solution containing a reducing group to obtain a precursor solution; (2) cleaning and hydrophilizing the substrate to obtain a pretreated substrate; (3) coating the precursor solution obtained in step (1) on the pretreated substrate obtained in step (2), and obtaining a precursor film after drying; (4) performing laser direct writing on the precursor film obtained in step (3) according to a preset pattern to obtain a multi-component doped supercapacitor electrode based on laser direct writing.

2. The preparation method according to claim 1, characterized in that: In step (1), the metal salt in the metal salt solution is selected from two or more of copper salts, nickel salts, silver salts, iron salts, manganese salts and cobalt salts.

3. The preparation method according to claim 1, characterized in that: In step (1), the concentration of the metal salt in the metal salt solution is 2 mol / L to 6 mol / L.

4. The preparation method according to claim 1, characterized in that: In step (1), the organic compound in the organic compound solution containing a reducing group is selected from one or more of polyvinyl pyrrolidone, formic acid, oxalic acid and polyethylene glycol.

5. The preparation method according to claim 1, characterized in that: In step (1), the concentration of the organic compound in the organic compound solution containing a reducing group is 0.1 g / mL to 0.3 g / mL; And / or, the volume ratio of the organic compound solution containing reducing groups to the metal salt solution is 3:1 to 1:

1.

6. The preparation method according to claim 1, characterized in that: In step (2), the substrate is selected from one of polyimide, polyethylene terephthalate and polycarbonate.

7. The preparation method according to claim 1, characterized in that: In step (3), the drying conditions are: drying at 70°C to 80°C for 10min to 15min.

8. The preparation method according to claim 1, characterized in that: In step (4), the parameters of the laser direct writing are: power 0.5W to 3W, spot diameter 20μm to 500μm, scanning interval less than 300μm, and scanning speed 5mm / s to 20mm / s.

9. A multi-component doped supercapacitor electrode based on laser direct writing prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the multi-component doped supercapacitor electrode based on laser direct writing according to claim 9 in the preparation of supercapacitors.

Citation Information

Cited By

  • Hydrogen sensor and preparation method thereof

    CN121877973A